The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1590/s0100-84551997000300005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of Prochilodus lineatus (Characiformes, Prochilodontidae) in the upper Paraná river

Abstract: The genetic variability of the "curimba", Prochilodus lineatus, from three locations in the Paraná river basin, was investigated by starch gel electrophoresis. A total of 160 specimens were analyzed for 19 enzymes, 12 of which permitted successful interpretation of electrophoretic patterns. Eighteen loci were identified and six of them proved to be polymorphic (EST-1*, EST-2*, IDH-1*, PGM-1*, PGM-2*, LDH-2*). Mean heterozygosity was considered high (13%) by comparison with the literature. A low level of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
2
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 17 publications
2
28
2
1
Order By: Relevance
“…Previous enzyme electrophoresis, used to quantify the genetic variations of P. lineatus collected from three sites in the Paraná river basin, detected no genetic divergences among the three samplings, suggesting a unique genetic pool of P. lineatus spread along the studied area (Revaldaves et al, 1997).…”
Section: Introductionmentioning
confidence: 78%
“…Previous enzyme electrophoresis, used to quantify the genetic variations of P. lineatus collected from three sites in the Paraná river basin, detected no genetic divergences among the three samplings, suggesting a unique genetic pool of P. lineatus spread along the studied area (Revaldaves et al, 1997).…”
Section: Introductionmentioning
confidence: 78%
“…Nevo (1978) estimated from data in the literature a mean P value of 15.2%, for 51 species of Teleostei. Studies carried out in fish species from Brazilian rivers show P values with a wide range of variation: Zawadzki (1996) found values from 11.45 to 19.23% in three species of the genus Hypostomus (Iguaçu River); Revaldaves et al (1997) observed 33.3% for Prochilodus lineatus (Paraná River) and Almeida and Sodré (1998) observed values from 6.67 to 20% in three Pimelodidae species (Tibagi River). Ward et al (1992) estimated an He value of 0.051 for about 150 marine and fresh water fish species.…”
Section: In Four Leporinus Species (Including L Friderici)mentioning
confidence: 99%
“…Marine fish populations have fewer barriers to gene flow and usually show less genetic differentiation than freshwater fishes (Gyllensten, 1985;Ward et al, 1994). Some migratory freshwater fish species such as P. lineatus (Revaldaves et al, 1997;Sivasundar et al, 2001) and P. corruscans (Sekine et al, 2002) show low genetic differentiation while poorly migratory or resident species such as H. malabaricus show high genetic differentiation (Dergam et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…The wide geographical range of H. regani not only contrasts with the narrow distribution of most Hypostomus species but can also raise doubts about the conspecificity of H. regani populations. Studies of the genetic population structure of Neotropical fish have mainly focused on known migratory species such as Prochilodus lineatus (Characiformes, Prochilodontidae) (Revaldaves et al, 1997) and Pseudoplatystoma corruscans (Siluriformes, Pimelodidae) (Sekine et al, 2002), with studies on nonmigratory fish having been restricted to Hoplias malabaricus (Characiformes, Erythrinidae) (Dergam et al, 1998;Peres et al, 2002). We have no data about migratory behavior of H. regani, whether it is resident, short, medium or long distance migratory.…”
Section: Introductionmentioning
confidence: 99%